2022
DOI: 10.1002/agj2.21212
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization strategy affects crop nutrient concentration and removal in semi‐arid U.S. Northwest

Abstract: Access to livestock manure is increasing in semi‐arid cropping systems of U.S. Northwest prompting evaluation of fertilization strategies on regional production systems. A study conducted from fall 2012 to 2019 used: fall‐ or spring‐applied dairy manure (56 Mg ha−1), fall‐applied composted dairy manure (33 Mg ha−1), spring‐applied urea or SUPERU (Koch Agronomic Services), and a control (n = 6) on a corn (Zea mays L.)–barley (Hordeum vulgare L.)–alfalfa (Medicago sativa L.)–alfalfa–alfalfa rotation. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
2
Order By: Relevance
“…With respect to EC, Bierer et al. (2023) found that EC increased due to recent manure applications, but in the present study, we found that after 11 years the EC of the manure treatments was similar to the non‐manure treatment. Because the irrigation water (from the Snake River) used in this study is relatively low in salts, any salts added in manure will be leached over time.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…With respect to EC, Bierer et al. (2023) found that EC increased due to recent manure applications, but in the present study, we found that after 11 years the EC of the manure treatments was similar to the non‐manure treatment. Because the irrigation water (from the Snake River) used in this study is relatively low in salts, any salts added in manure will be leached over time.…”
Section: Resultscontrasting
confidence: 79%
“…Studies in Idaho have shown that dairy manure generally does not increase soil pH due to the high buffer capacity of alkaline calcareous soils (Baxter et al, 2023;Dungan et al, 2022). With respect to EC, Bierer et al (2023) found that EC increased due to recent manure applications, but in the present study, we found that after 11 years the EC of the manure treatments was similar to the non-manure treatment. Because the irrigation water (from the Snake River) used in this study is relatively low in salts, any salts added in manure will be leached over time.…”
Section: Chemical Propertiescontrasting
confidence: 70%